Respectful Attitude on Adolescents to Elderly - Utari, Alisa Putri; Sulandari, Santi (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: Respect is an attitude that must be possessed by every teenager, because respect requires everyone to always appreciate and love one another. Unfortunately, the majority of adolescents today lack of respectful attitude toward older people, especially towards the elderly. The purpose of this study is to find out and describe the attitude of respect for adolescents towards the elderly. Methods: This research is a descriptive qualitative research. Data collection techniques in this study used an open questionnaire and involved 105 adolescents aged 13 to 18 years old who came from five schools, namely private, regular, and public private schools in the Surakarta region. Then the data analysis used is interactive analysis. Results: The results showed that respect for adolescents towards the elderly can be seen from three forms of attitude, namely: 1) how to communicate; 2) posture; and 3) prosocial behavior. Factors that influence respect for adolescents towards the elderly are divided into personal factors and situational factors. Personal factors (within) include emotional factors of each different individual, adolescents will be respectful when they are able to control the feelings / emotions that are being felt. Whereas situational factors (from outside) include environmental or cultural factors and influences from others that are considered important.Value: Therefore, it is very important for policy makers to be able to help foster respect for adolescents through strengthening these factors.